Connecting the next billion web users - Rastogi, Rajeev; Cutrell, Ed; Gupta, Manish; Jhunjhunwala, Ashok; Narayan, Ramkumar; Sanghal, Rajeev (Proceedings of the 20th international conference companion on World wide web, 2011)
With 2 billion users, the World Wide Web has indeed come a long way. However, of the 4.8 billion people living in Asia and Africa, only 1 in 5 has access to the Web. For instance, in India, the 100 million Web users constitute less than 10% of the total population of 1.2 billion. So it is universally accepted that the next billion users will come from emerging markets like Brazil, China, India, Indonesia and Russia. Emerging markets have a number of unique characteristics: Large dense populations with low incomes Lack of infrastructure in terms of broadband, electricity, etc. Poor PC penetration due to limited affordability High illiteracy rates and inability to read/write Plethora of local languages and dialects General paucity of local content, especially in local languages Explosive growth in the number of mobile phones The panel will debate the various technical challenges in overcoming the digital divide, and potential approaches to bring the Web to the underserved populations of the developing world.